STRATEGI KOMUNIKASI KEPALA MADRASAH TERHADAP KINERJA GURU MTS NURFADHILAH GOWA - Sakina Arjuni; Sitti Mania; Ermi Sola (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the communication strategies of the madrasah principal towards teacher performance at MTs Nurfadhilah Gowa in terms of communicators, messages, media, and targets. This study uses a qualitative descriptive approach. Data were obtained through observation, interviews, and documentation from primary sources (the Madrasah Principal, Deputy Madrasah Principal, and Teachers) as well as secondary sources. Data analysis techniques include reduction, presentation, and drawing conclusions, with validity maintained through triangulation. The results show that the madrasah principal's communication strategies towards teacher performance have been structured and have made a significant contribution to improving student learning achievement. First, the communicator is carried out by the madrasah principal transparently and with consistent discipline. Second, information messages in the madrasah have succeeded in building teacher trust. Third, the media used harmoniously combines structural and digital aspects. Fourth, the message targets have succeeded in building inclusive and accommodating communication patterns through several strategies. Overall, the madrasah principal's communication strategies towards teacher performance have been structured and have made a significant contribution to improving student learning achievement.